EFFECT OF CHRONIC TOBACCO USE ON SALIVARY CONCENTRATIONS OF SODIUM AND POTASSIUM - Khan, Ghulam Jillani; Mehmood, Rashid; Din, Salah -ud-; Haq, Ihtesham -ul- (Journal of Ayub Medical College Abbottabad, 2003)
Background: Most of the methods of tobacco are use linked to the oral cavity where the taste receptors, a primary site for stimulation of salivary secretion, are constantly exposed to tobacco. It is generally believed that repeated exposure of a receptor to a stimulus results in inactivation (suppression) of the receptor. The present study was designed to document changes in salivary concentrations of sodium (Na+) and potassium (K+) in response to this effect in chronic tobacco users. Methods: Subjects of the study were divided into smokers, pan (tobacco-betel-lime quid) chewers, niswar (moist oral snuff) differs and non tobacco users as controls. The saliva of each subject was collected under resting condition and following application of crude nicotine and citric acid solutions to the tip of his tongue. Results: After stimulation with nicotine all groups exhibited an increase in sodium concentration but the increase was significant (p<0.05) in pan chewers only. However all groups showed a highly significant (p<0.005) increase in sodium concentration after citric acid stimulation. No statistically significant (p>0.05) decrease in potassium concentration was observed in any group after nicotine stimulation but all chronic tobacco user groups showed a highly significant (p<0.005) decrease after citric acid stimulation. Conclusion: We conclude the sodium concentration increases and that of potassium decreases with the increase in salivary flow rates and this observation in chronic tobacco users was not much different from that in non tobacco users. Keywords: Saliva, tobacco, sodium, potassium